Determination of Atropine in Injection with ÃŽÂ²-Cyclodextrin Modified Ion Sensitive Field Effect Transistor Sensor - Hong-Ye Lin; Ying-Ying Wu; Bo-Lun Yang; Xian-Wen Li (Sensors, 2005)
A new atropine drug-FET sensor, which was made of an ISFET (ion sensitivefield effect transistor) and a drug sensitive membrane prepared by adding electric activematter to a ÃŽÂ²-cyclodextrin solution, was developed. The pH influence, selectivity, responsecurve, reproducibility, stability, response time and life of this sensor were investigated. Apreliminary application of the sensor was discussed as well. The experimental resultsindicated that the sensor showed a Nernst response to atropine with a slope of 58.0mV/decade over the concentration range of 5.0ÃƒÂ—10-3 Ã¯Â¼Â 1.0ÃƒÂ—10-6 mol/L and the pH rangeof 5.0Ã¯Â¼Â8.5. The sensor detection limit was 8.0ÃƒÂ—10-7 mol/L. The performance of this sensorwas very stable when it was used to determine atropine concentration in a medicinalinjection. The obtained results agreed well with the pharmacopoeia method.